Sports training for 16-17 years old skiers-racers in mid-mountain conditions - Bezmaternykh, I. S.; Gorbunov, S. S.; Kostareva, S. V.; Ibragimov, R. R. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effectiveness of various approaches to the organization of the training process of 16-17 year old ski-racers in the competitive period in mid-mountain conditions.